Validation of 13C-urea Breath Test for the Diagnosis of Helicobacter pylori Infection Among Dyspeptic Patients at Dr Soetomo Hospital Surabaya - Herry Purbayu; Poernomo Boedi Setiawan; Iswan A Nusi; Pangestu Adi; Hernomo Ontoseno Kusumobroto (The Indonesian Society for Digestive Endoscopy, 2007)
Background: The urea breath test (UBT) has been published as the most sensitive and specific non-invasive test to detect Helicobacter pylori (H. pylori) infection. The limitation of UBT is the need of expensive equipment that is not always widely available. Recently, UBT has already been available in Surabaya. In the other hand, our experience using rapid urease test which detected urease enzyme produced by H. pylori as UBT showed low sensitivity. Objective: To investigate the validation of UBT for the diagnosis of H. pylori infection in patient with dyspepsia. Design: Cross-sectional study. Method: Sixty patients who complained symptoms of dyspepsia were examined for H. pylori infection using UBT. Gastroscopy and biopsy was were performed and the biopsy specimens were examined by Pathologist. Results: Sixty patients consist of 28 male and 32 female were enrolled of this study. Eight patients had H. pylori positive by both UBT and histologic examination. One patient was H. pylori positive by UBT but negative by histologic examination. One patient was H. pylori negative by UBT but positive by histologic examination. The sensitivity of UBT was 88.9% and the specificity was 98 %. The negative predictive value was 98%. Conclusion: In this study, UBT has lower sensitivity (88.9%) and comparable specificity (98%) for diagnosing H. pylori infection. Comprehensive studies to determine the doses of 13C-urea, test meal and appropriate collection time, which is more suitable for local population was suggested. Keywords: 13C-Urea Breath Test, Helicobacter pylori, dyspepsia, diagnosis